2011
DOI: 10.1017/s1751731110001965
|View full text |Cite
|
Sign up to set email alerts
|

Performance and plasma metabolites of dairy calves fed starter containing sodium butyrate, calcium propionate or sodium monensin

Abstract: This study was conducted to examine the influence of supplementation of sodium butyrate, sodium monensin or calcium propionate in a starter diet on the performance and selected plasma metabolites (plasma glucose, non-esterified fatty acids and b-hydroxybutyrate) of Holstein calves during pre-and post-weaning periods. Twenty-four newborn Holstein calves were housed in individual hutches until 10 weeks of life, receiving water free choice, and fed four liters of milk daily. Calves were blocked according to weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
24
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 36 publications
14
24
2
1
Order By: Relevance
“…Thus, our VFA data support the theory that elevating DMI may improve VFA concentration and rumen development, particularly in young calves. Ferreira & Bittar (2011) demonstrated that physical traits such as wither height, heart girth and hip width of calves improved when their milk replacer was supplemented with sodium butyrate, which conforms with the results of present study. Increase in DMI and improvement of physical traits suggest that CCB, together with high-quality milk replacer and starter, has a major impact on calves' growth within a short period of time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, our VFA data support the theory that elevating DMI may improve VFA concentration and rumen development, particularly in young calves. Ferreira & Bittar (2011) demonstrated that physical traits such as wither height, heart girth and hip width of calves improved when their milk replacer was supplemented with sodium butyrate, which conforms with the results of present study. Increase in DMI and improvement of physical traits suggest that CCB, together with high-quality milk replacer and starter, has a major impact on calves' growth within a short period of time.…”
Section: Discussionsupporting
confidence: 92%
“…A simple explanation for the increased serum BHBA concentration in CCB group was daily butyrate intake. Another putative consequence of elevated serum concentration of BHBA, which is confirmed by Ferreira &Bittar (2011) andYari et al (2010), is that the increased starter intake resulted in a higher rumen VFA production.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Even though supplementation with EO blend did not affect (P > 0.05) BW and average daily gain (Figure 2), there was a significant effect of age for these variables (P < 0.0001; Table 2), which progressively increased until the 10 th week of life. The weight gain values are similar to those found by Ferreira and Bittar (2011), in similar housing and climate conditions, when additives to improve the overall performance of dairy calves were tested.…”
Section: Resultssupporting
confidence: 80%
“…However, since calves were growing, there was a significant age effect (P < 0.0001) for all measures. Observed body measurements are slightly lower than those found by Ferreira and Bittar (2011), with sodium propionate supplementation as an alternative to antibiotics in similar experimental conditions.…”
Section: Resultscontrasting
confidence: 62%